Principles of political parties - McDonald, David Collins (My University, 1891)
Introduction: In a popular government, parties are a necessity. To demonstrate this fact we need only imagine an election where there were no parties to place in nomination tickets representing certain ideas and principles. Imagine each citizen going to the polls and casting his ballot for his individual choice for the office of president. Imagine, if you can, the endless confusion that would result from such an election, if indeed you can think that our election would be possible in such a manner in this vast republic. Only in a few exceptional cases would a man thus chosen represent the choice or the principles of the majority. Indeed, he could hardly be said to represent any principles. But in governments, principles should rule and not men, so long as a man is trustworthy and performs the duties of his office faithfully, he is and should be a secondary consideration. Compare with this the party system in its purity—not as men have corrupted it—by which a few candidates representing definite formulated principles are placed before the people for their rejection or approval. A man so chosen may reasonably be expected to do his best to put into practice the principles upon which he was elected.
Citation: McDonald, David Collins. Principles of political parties. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Election; Politics; Presidency; Ballot; Republic; Political science; Theses; Manuscripts (documents)